Secularism, Islamisation and Humanism: Which Permutation for Religious Tolerance and Harmony? - Faris Bin Ridzuan
In multiethnic, multireligious, and multicultural Singapore, Singapore's brand of secularism that guarantees freedom of religious belief, practice, and expression, alongside the government's policies of fostering social cohesion, have been key contributors to Singapore's burgeoning religious pluralism, tolerance, mutual understanding, care, and concern. However, a growing and influential episteme that might challenge Singaporean Muslims’ acceptance of Singapore's brand of secularism is the Islamisation of knowledge discourse, which was a response to Islamic revivalism which spread globally since the 1970s. This episteme has even influenced local asatizah, who have misgivings about Singapore's secularism despite living in a secular country. For Singapore and Malaysia, there are two relevant and dominant perspectives on the Islamisation of knowledge - one by Ismail Farugi and the other by Syed Naquib Al-Attas. Faruqi's perspective is positivisticand only addresses the Islamisation of knowledge of subjects in terms of their forms, and not the substantive essence of the subjects. For Al-Attas, what matters is the Islamisation of epistemology and metaphysics of knowledge rooted in the Sufi-inspired Islamisation of the mind, worldview, and perspective. As a result of the possibility of interpreting the works of Al-Attas from a revivalist and Islamist orientation, many Muslims from Singapore and Malaysia who follow the works of Al-Attas, especially his more ideological work “Islam and Secularism”, are antagonistic towards secularism and this is very problematic for a secular context like Singapore. The ideological work